1990
DOI: 10.1016/0378-1119(90)90289-4
|View full text |Cite
|
Sign up to set email alerts
|

Two subfamilies of murine retrotransposon ETn sequences

Abstract: Early transposon (ETn) elements are 5.7-kb retrotransposons found in the murine genome. We have sequenced large portions of two ETn elements that have apparently transposed within the DNA of a murine myeloma cell line, P3.26Bu4. One of the transposed ETn elements has 5' and 3' long terminal repeats (LTRs) that are exact duplicates of each other and has a 6-bp target site duplication. These results suggest that this element, which inserted into an immunoglobulin gamma 1 switch region, moved by a retrotransposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Previous studies identified a single site of transcription initiation at the border of the U3 and R regions in the ETn LTR in primary acute myeloid leukemia (56) and carcinoma (20) cells. However, the elements investigated in those studies belong to the ETnI family and thus differ significantly from the ETnII elements studied here in the 3Ј ends of their LTRs and part of the downstream sequence (4,49). Although the presumed U3 region is nearly identical in both families, highly divergent U5 and downstream sequences may play a role in variable transcription initiation between ETnI and ETnII elements.…”
Section: Mutational Analysis Of the Etnii Ltrmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies identified a single site of transcription initiation at the border of the U3 and R regions in the ETn LTR in primary acute myeloid leukemia (56) and carcinoma (20) cells. However, the elements investigated in those studies belong to the ETnI family and thus differ significantly from the ETnII elements studied here in the 3Ј ends of their LTRs and part of the downstream sequence (4,49). Although the presumed U3 region is nearly identical in both families, highly divergent U5 and downstream sequences may play a role in variable transcription initiation between ETnI and ETnII elements.…”
Section: Mutational Analysis Of the Etnii Ltrmentioning
confidence: 81%
“…ETn elements were originally divided into two groupsETnI and ETnII-which differ only in the 3Ј one-third of the long terminal repeat (LTR) and the 5Ј end of the adjacent internal region (20,49,51). The rest of the internal region contains mainly nonretroviral, noncoding sequences of unknown origin, with the exception of a short stretch of a retroviral pol gene (31).…”
mentioning
confidence: 99%
“…ETn transcripts are presumably recognized by reverse transcriptase and other proteins encoded by another type of endogenous retrovirus or retrotransposon, but the identity of these putative coding-competent elements is unknown. Interestingly, it was noted several years ago (23) that new ETn insertions into the immunoglobulin (Ig) region in cell lines are members of a subfamily which differ completely from the first randomly isolated elements in the 3Ј part of the LTR and approximately 300 bp of sequence just internal to the 5Ј LTR-a region which typically contains the retroviral packaging signal (8). It was therefore suggested that this sequence difference allows members of the "active" ETn subfamily to be preferentially packaged and to retrotranspose (23).…”
mentioning
confidence: 99%
“…[24][25][26][27][28] Genomic PCR with primers 67 or 35 paired with primers specific for the long terminal repeat (LTR) of ETn transposons (kindly provided by V. Letts, The Jackson Laboratory) failed to yield products (data not shown). Amplification using primers 67 or 35 paired with primers specific for IAP LTRs (69 and 69r, Figure 4A; kindly provided by B. Gwynn, The Jackson Laboratory) generated products from sph Dem /sph Dem and sph Dem /ϩ DNA, but not from ϩ/ϩ DNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%